Implementasi Security Information adn Event Management (SIEM) pada Sistem Akademik Universitas Kuningan - Nugraha, Fitra; Khalimi, Toni; Herwanto, Heri (Buffer Informatika, 2025)
This research aims to implement Security Information and Event Management (SIEM) in the Kuningan University academic system. The security of information systems in the educational environment, especially in university academic systems, is becoming increasingly important considering the availability of sensitive data, such as student personal information and academic data which must be properly protected. Security threats such as cyber attacks are increasingly complex and can often be detrimental to both universities and system users. In this research, we apply SIEM as a solution to detect, prevent and respond to security threats to the Kuningan University academic system. The system development method is used with the steps of system requirements analysis, system design, system implementation, system testing, and system evaluation. The output of this research is an increase in the security level of Kuningan University's academic system. By implementing SIEM, the system is expected to be able to quickly and effectively detect potential security threats, improve response to security events, and provide reports that are useful for making decisions. Thus, it is hoped that the results of this research can make a significant contribution in improving security and data protection in the Kuningan University academic system, as well as becoming a reference for other educational institutions in maintaining increasingly complex information security defenses.